The Pre-Ablation Circulating Tumor-Associated Inflammatory Index Predicts the Prognosis of Patients with Liver Metastasis from Pancreatic Cancer - Li Y; Peng L; Zhang K; Wu Y; Gao H; Chen H (Dove Medical Press, 2022)
Yujie Li,1,2 Linjia Peng,1,2 Ke Zhang,1,2 Yong Wu,3 Huifeng Gao,1,2 Hao Chen1,2 1Department of Integrative Oncology, Fudan University Shanghai Cancer Center, Shanghai, People's Republic of China; 2Department of Oncology, Shanghai Medical College, Fudan University, Shanghai, People's Republic of China; 3Department of Oncology, The Second Affiliated Hospital of Anhui University of Traditional Chinese Medicine, Hefei, People's Republic of ChinaCorrespondence: Hao Chen, Department of Integrative Oncology, Fudan University Shanghai Cancer Center, 270 Dong'an Road, Shanghai, People's Republic of China, Tel +86-18017312356, Email chengkll@sina.comObjective: Ablation serves as a common local treatment for liver metastases from pancreatic cancer (PCLM), but the correlation between the prognosis of PCLM and inflammatory cytokines has been rarely reported. This study aimed to establish a cytokine-based prognostic model for patients with PCLM who are receiving ablation.Patients and Methods: Serum samples from peripheral blood were collected from patients with PCLM before their first ablation. Cytokines were measured using Luminex chips and ELISA. Cox regression and least absolute shrinkage and selection operator regression were used to select prognostic factors for overall survival (OS). Area under the receiver operating characteristic curve (AUC) was applied to compare the ability to predict survival.Results: The relationship between cytokines and clinical factors was evaluated and their prognostic value was compared. Six optimal predictors were selected, including IL-2, IL-7, HGF, IFN-γ, CA19-9 and CEA. The risk model based on these predictors was built and named circulating tumor-associated inflammatory index (CTII). The CTII (AUCs > 0.90) showed superior performance to systemic immune-inflammation index (SII, AUCs < 0.65) in OS.Conclusion: A circulating cytokine-based risk model for patients with PCLM before first ablation has been proposed and validated, which has demonstrated superior performance in predicting survival and has the potential to inform clinical treatment strategies.Keywords: inflammation, cytokines, advanced pancreatic cancer, ablation, prognosis